Cotesia itororensis sp. nov. from Brazilian savanna: a new reared microgastrine wasp (Hymenoptera: Braconidae) described using an integrative taxonomic approach - de Sousa-Lopes, Bruno; Whitfield, James Bryan; Salgado-Neto, Geraldo; Del-Claro, Kleber (Zootaxa, 2019)
A new species of microgastrine wasp, Cotesia itororensis Sousa-Lopes & Whitfield, sp. nov., is described from a Brazilian savanna area in Uberlândia, Minas Gerais. This species is a koinobiont endoparasitoid recorded from caterpillars of Oospila pallidaria (Schaus, 1897) (Lepidoptera: Geometridae), feeding on Mimosa setosa var. paludosa (Fabaceae: Mimosoideae). Morphological, molecular, biological, ecological and geographical data are used to describe the new species and distinguish it from others formally recorded for the Neotropical region.